Anemia in traumatic brain injury: when to transfuse? - Tiago dos Santos Soares Harper Maia (2019)
Purpose of review: Patients with traumatic brain injury (TBI) are typically multiple trauma patients, presenting with various pathological entities that jeopardize their survival. Anemia is one of the most common abnormalities in trauma patients, and is considered a worse prognosis determinant. However, strong recommendations, and high-quality prospective studies to support them, about the best transfusion practices in brain trauma patients are scarce, if not inexistent, leading to major doubts in optimal treatments. This review's intention is to summarized actual evidence regarding this issue, mainly the hemoglobin thresholds and other important triggers used in treating anemic TBI patients. Recent findings: In general intensive and neurocritical care, a restrictive transfusion method has been proven safe and, at least, not inferior to previously advocated liberal thresholds. Nevertheless, another physiological variables have been recently studied in treating anemia in this patients' population, leading to more liberal approaches in red blood cell transfusions, due to recent implemented "triggers". Allowing a normal oxygen delivery and achieving an optimal brain oxygenation is dependent of multiple factors, independent of hemoglobin concentrations. Summary: Nowadays, there is no sufficiently high-quality information to provide practicians with strong general recommendations in managing anemia in traumatic brain injury. Transfusions are one of the main options, but they have both benefits and risks that must be taken in account in every single case.